Molecular Structural Characterization of Cycloparaphenylene and its Variants. (14th September 2022) - Prabhu, S.; Murugan, G.; Therese, S. Kulandai; Arulperumjothi, M.; Siddiqui, Muhammad Kamran
Abstract: Conjugated aromatic macrocycles are engaging due to their remarkable photophysical and optoelectronic properties. Specifically, the cyclic radially-oriented π -arrangement of cycloparaphenylenes (CPPs) offers to ascend to photophysical properties dissimilar to small particle or carbon nanomaterial. A couple of sizes of CPPs, CPP derivatives, and related carbon nanorings have been integrated and their entrancing properties have gotten uncovered. Structure-based topological indices of these frameworks empower expectation of chemical properties and the bioactivities of these compounds through quantitative structure-activity and structure-property connections strategies. In this article, we derive the mathematical expression of CPP and its side wall contains pyrene and hexabenzocorenene.